Physical Simulator Of Infrared Spectroradiometer With Spatial Resolution Enhancement Using Subpixel Image Registration And Processing - Lyalko, V.І.; Popov, M.A.; Stankevich, S.A.; Shklyar, S.V.; Podorvan, V.N.; Likholit, N.I.; Tiagur, V.M.; Dobrovolska, C.V. (Science and Innovation, 2024)
The mathematical and physical models of new frame IR spectroradiometer based on microbolometer detector array with subpixel image registration have been presented. The radiometer is planned to be incorporated into the onboard instrumentation of Sich satellite system for obtaining the earth surface physical parameters from the data of aerospace IR survey with enhanced spatial resolution.